STRATEGI PENGEMBANGAN AGRIBISNIS AYAM RAS PETELUR PADA CV. BINTANI POULTRY SHOP KENDARI - Musram Abadi; Sitti Aida Taridala; La Ode Nafiu (Universitas Halu Oleo, 2016)
The research was conducted to analyze and identify supporting and inhibiting factors, arranging layer farm agribusiness development strategy on CV Bintani Poultry Shop Kendari. This research was held on 2012. The research variables were (a) layer farm business characteristic and (b) strength, weakness, threat, and opportunity. The agribusiness development strategy aspect analysis was using SWOT and QSPM analysis. Research result showed that production capacity increasing strategy and quality increasing and worker quantity were scored 6,146, and 5,375 respectively. Meanwhile technology application on layer farming practice and others livestock business development were scored 5,303 and 4,220 respectively. Key words: Agribusiness, Layer Farm, Development Strategy